2019
DOI: 10.2135/cropsci2018.07.0468
|View full text |Cite
|
Sign up to set email alerts
|

Sugarcane Straw Blanket Management Effects on Plant Growth, Development, and Yield in Southeastern Brazil

Abstract: In Brazilian sugarcane (Saccharum spp.) production systems, the practice of moving harvesting residue from row to inter‐row positions (i.e., raking) has increased in response to producer concerns over the potential negative effects of sugarcane straw on crop establishment and stalk yield. Despite increasing adoption among sugarcane farmers, the impacts of straw raking practices on plant growth and yield remain unclear. A 2‐yr experiment that included both dry and wet seasons was conducted at two sites in south… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 56 publications
1
3
0
1
Order By: Relevance
“…In Brazil, other authors have reported reductions of 0.01 and 0.08 g g -1 due to straw removal (Peres et al, 2010;Awe et al, 2015;Corrêa et al, 2019). Our data is also in line with previous simulations performed by Gmach et al (2019), who estimated that the complete maintenance of straw (12 Mg ha -1 ) or even partial maintenance (6 Mg ha -1 ) delays the water-limiting condition in plants for approximately one month compared to bare soil (total removal) during the dry season in the state of São Paulo. However, even an increase of 0.03 g g -1 in soil moisture noted in medium soil represents a gain of about 64 L m 2 (four-day water supply for the crop).…”
Section: Effect Of Sugarcane Straw Removal On Soil Moisturesupporting
confidence: 93%
See 1 more Smart Citation
“…In Brazil, other authors have reported reductions of 0.01 and 0.08 g g -1 due to straw removal (Peres et al, 2010;Awe et al, 2015;Corrêa et al, 2019). Our data is also in line with previous simulations performed by Gmach et al (2019), who estimated that the complete maintenance of straw (12 Mg ha -1 ) or even partial maintenance (6 Mg ha -1 ) delays the water-limiting condition in plants for approximately one month compared to bare soil (total removal) during the dry season in the state of São Paulo. However, even an increase of 0.03 g g -1 in soil moisture noted in medium soil represents a gain of about 64 L m 2 (four-day water supply for the crop).…”
Section: Effect Of Sugarcane Straw Removal On Soil Moisturesupporting
confidence: 93%
“…This improvement would be associated with: i) greater heating of the soil without straw; ii) increase in the intensity and amount of solar radiation that reaches the sugarcane ratoon; iii) removal of the physical barrier formed by the straw left on the sugarcane ratoon. All these effects induced the sugarcane sector to adopt the raked (raking straw to inter-rows) practice, which recently discovered that, despite providing these benefits in the initial period of plant development, failed to generate increases in productivity (Lisboa et al, 2019).…”
Section: Effects Of Sugarcane Straw Removal On Soil Temperaturementioning
confidence: 99%
“…These conditions potentially improve plant growth and, consequently, phytomass yield. Although we strongly recognize that it is mandatory to consider specific edaphoclimatic conditions to perform sustainable straw removal, our findings provide relevant understanding about why moderate straw removal has been suggested in several studies in which straw removal management was framed [15,24,55,57].…”
Section: Effects Of Straw Removal On Sugarcane Yieldmentioning
confidence: 83%
“…However, straw maintenance higher than 10 Mg ha −1 is also associated with a reduction in plant sprouts, stalk yield [24,25] and sucrose concentration in stalks [56], particularly in the region where the study was conducted, which is cooler than other sugarcane-producing regions in Brazil [25]. Overall, decreasing of initial sugarcane phytomass yield (tillering) occurs even under lower quantities of straw; this is especially remarkable under cooler regions [24], but in most cases, the crop is able to recover from the negative impacts caused by straw retention in earlier growth stages [15,24,57].…”
Section: Effects Of Straw Removal On Sugarcane Yieldmentioning
confidence: 99%
“…Por lo cual, se deben buscar estrategias para incrementar los rendimientos y mejorar la tasa de descomposición y liberación de N en el ciclo de cultivo. De lo contrario, la acumulación de residuos a largo plazo podría mostrar efectos negativos en la producción de biomasa, productividad y limitar labores agrícolas, así como aumentar la incidencia de plagas y enfermedades y la liberación de N2O y CO2, con los subsecuentes incrementos de costos (Campos, 2010;Fortes et al, 2012;Dinardo-Miranda y Fracasso, 2013;Vargas et al, 2014;Lisboa et al, 2019). La dinámica de descomposición y liberación de nutrientes dependerá de la variedad de caña, la edad del cultivo, el tipo de suelo, condiciones climáticas y microorganismos del suelo (Oliveira et al, 2003;Fortes et al, 2012;Marin et al, 2014).…”
Section: Introductionunclassified